ANALISIS HUBUNGAN EARNING PER SHARE DENGAN PROFITABILITAS PADA PERUSAHAAN YANG GO PUBLIC DI BURSA EFEK INDONESIA - Yohandes Rabiqy (JURNAL EKOMBIS, 2018)
The objective of this research is to examine the correlation between EPS and Profitability of Food and Beverages Corporation that are listing in Indonesian stock exchange. Data is collected from Indonesian stock exchange (BEJ). In this research, we used several indicators to observed the profitability , they are operating profit margin, earning power, net profit margin, return on investment and return on equity. Pearson’s product moment correlation was implemented to examine the correlation between EPS and Profitability. The result shows that some factors of profitability are significantly positive correlation to EPS except operating profit margin.Keywords: EPS and profitability.